2011
DOI: 10.2174/187152011795255911
|View full text |Cite
|
Sign up to set email alerts
|

Manganese Superoxide Dismutase (Sod2) and Redox-Control of Signaling Events That Drive Metastasis

Abstract: Manganese superoxide dismutase (Sod2) has emerged as a key enzyme with a dual role in tumorigenic progression. Early studies were primarily directed at defining the tumor suppressive function of Sod2 based on its low level expression in many tumor types. It is now commonly held that loss of Sod2 expression is likely an early event in tumor progression allowing for further propagation of the tumorigenic phenotype resulting from steady state increases in free radical production. Increases in free radical load ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
145
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(159 citation statements)
references
References 102 publications
11
145
2
1
Order By: Relevance
“…Furthermore, in LC patients with COPD, the heaviest smokers were those showing the decrease in catalase levels in the tumor lesions compared to the nontumor lungs (26). These findings are consistent with other studies in which catalase deficiency was shown to contribute to mammary tumorigenesis in rodents (119) and cancer in patients (37). Collectively, it would be possible to conclude that catalase depletion seems to be involved in cancer development, especially in LC patients with underlying COPD, especially in those who were heavy smokers.…”
Section: Reactive Oxygen Speciessupporting
confidence: 91%
“…Furthermore, in LC patients with COPD, the heaviest smokers were those showing the decrease in catalase levels in the tumor lesions compared to the nontumor lungs (26). These findings are consistent with other studies in which catalase deficiency was shown to contribute to mammary tumorigenesis in rodents (119) and cancer in patients (37). Collectively, it would be possible to conclude that catalase depletion seems to be involved in cancer development, especially in LC patients with underlying COPD, especially in those who were heavy smokers.…”
Section: Reactive Oxygen Speciessupporting
confidence: 91%
“…In fact, a recent study (24) demonstrated that inhibition of SOD activity reduced tumor burden in mice and promoted cell death in several lines of NSCLC lines of cells. Furthermore, SOD2 was shown to favor cell migration and invasiveness of tumors in other investigations (43,44). More recently, mRNA and protein levels of SOD2 were also significantly increased in lung tumors and other cancer types in patients (25).…”
Section: Discussionmentioning
confidence: 82%
“…When tumor progresses more aggressive, MnSOD is upregulated. MnSOD level positively correlates with increased metastasis so MnSOD has an oncogene role (Hempel, et al, 2011;Dhar, et al, 2011). Increase in MnSOD level was seen during the progression of different types of tumors, including brain, to the metastatic stage.…”
Section: Antioxidant Status Of the Brainmentioning
confidence: 99%
“…The coexpression of catalase was shown to revert malignancy (Hempel, et al, 2011). The overexpression of catalase protected cancer cell from excessive peroxide production as a result of combined menadione/ascorbate anticancer treatment (Glorieux, et al, 2011).…”
Section: The Potential Therapy In Brain Tumors Regarding Antioxidantsmentioning
confidence: 99%